2005
DOI: 10.1124/dmd.105.006643
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Metabolism of a Selective Androgen Receptor Modulator in Rats: Implication of Molecular Properties and Intensive Metabolic Profile to Investigate Ideal Pharmacokinetic Characteristics of a Propanamide in Preclinical Study

Abstract: Androgens play important roles in male phenotype development and maintenance of male and female physiology and reproduction (Mooradian et al., 1987). Testosterone and 5␣-dihydrotestosterone are the two main endogenous steroidal androgens involved in reproductive and nonreproductive tissue. Synthesized steroidal androgens have been used as therapeutic agents to treat a broad spectrum of disorders due to androgen deficiency. However, androgen preparations available in the market exhibit severe limitations. Testo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 36 publications
4
21
0
2
Order By: Relevance
“…Although N-methylation of amides is rare, the presence of the amide carbonyl and para-nitro substituent on the adjoining aromatic ring makes this an acidic proton and increase the likelihood of N-methylation. Previous in vitro and in vivo metabolism studies with a close structural relative of S-4 demonstrated that N-methylation occurs in the aryl propionamide SARMs (Wu et al, 2006). Furthermore, tandem mass spectrometry spectra of the S4-CH 3 metabolite were similar to those of synthetic standards of N-methylated aryl propionamide SARMs previously reported by our laboratories (Patil et al, 2006).…”
Section: Metabolite S4-ch 3 (M/z 454) This [M ϫ H]supporting
confidence: 57%
“…Although N-methylation of amides is rare, the presence of the amide carbonyl and para-nitro substituent on the adjoining aromatic ring makes this an acidic proton and increase the likelihood of N-methylation. Previous in vitro and in vivo metabolism studies with a close structural relative of S-4 demonstrated that N-methylation occurs in the aryl propionamide SARMs (Wu et al, 2006). Furthermore, tandem mass spectrometry spectra of the S4-CH 3 metabolite were similar to those of synthetic standards of N-methylated aryl propionamide SARMs previously reported by our laboratories (Patil et al, 2006).…”
Section: Metabolite S4-ch 3 (M/z 454) This [M ϫ H]supporting
confidence: 57%
“…4A shows the proposed fragmentation ions of S-26. Similar metabolic pathways of SARMs were reported also previously by our laboratory (23)(24)(25). The product ion at m/z 299 corresponds to a cleavage of the bond between the chiral carbon and methylene carbon with loss of a methyl group.…”
Section: Identification Of Major Metabolites Of S-26 In Rat Urine Andsupporting
confidence: 58%
“…Among all tissues, the thyroid gland accumulated the highest percentage of radioactivity at all three time points, suggesting that S-26 was extensively de-iodinated in vivo, which was further confirmed by our metabolism studies using rat urine and feces. The deiodination of S-26 represented a different metabolic pathway of SARMs comparing to the metabolism studies previously reported by our laboratory (23)(24)(25). The high accumulation of radioactivity by GI tract and a large proportion of radioactivity in urine are also indications of release of free iodine from the parent drug in vivo.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Similar strategies have been employed in the development of selective estrogen receptor modulators or SERMs including tamoxifen and raloxifene, which exhibit tissue-specific estrogen receptor agonist (e.g., bone, uterus) and antagonist (e.g., breast) actions (Musa et al, 2007). Recently, several new SARMs have been developed that exhibit tissuespecific AR agonist activity (Kearbey et al, 2007;Ostrowski et al, 2007;Wu et al, 2006), although their actions in brain have yet to be reported.…”
Section: Antiandrogens and Ar-dependent Neuroprotectionmentioning
confidence: 99%